Single‐Source Precursor‐Based Deposition of Sb2Te3 Films by MOCVD**1. Issue 7 (7th August 2013) - Bendt, Georg; Schulz, Stephan; Zastrow, Sebastian; Nielsch, Kornelius
Abstract : The low‐temperature metal‐organic (MO)CVD of Sb2 Te3 films is achieved by the use of the single‐source precursor (Et2 Sb)2 Te, 1 . The role of the substrate temperature on the deposition rate and the composition of the resulting film is described. The resulting Sb2 Te3 films are characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X‐ray (EDX) and Auger spectroscopies. Moreover, the Seebeck coefficient of the Sb2 Te3 film deposited at 200 °C is determined, and the value of 160 µV K −1 demonstrates the high quality and low carrier density of the film. Abstract : (Et2 Sb)2 Te is a volatile, single‐source‐precursor for the MOCVD of Sb2 Te3 films at low temperatures. The growth rates increase from 600 nm h −1 at 200 °C with increasing substrate temperature. The Sb2 Te3 films consist of randomly oriented hexagonal nanoplates with a diameter of more than 2 µm. In addition, Seebeck coefficients of up to 160 µV K −1 demonstrate the high quality and low carrier density of the Sb2 Te3 films.